2021
DOI: 10.1371/journal.pntd.0009241
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral miltefosine in treatment of antimoniate resistant anthroponotic cutaneous leishmaniasis: An uncontrolled clinical trial

Abstract: Background Recent circumstantial evidence suggests increasing number of Iranian patients with cutaneous leishmaniasis (CL) who are unresponsive to meglumine antimoniate (MA), the first line of treatment in Iran. Oral meltifosine was previously reported to be effective in visceral leishmaniasis as well CL. The current study is designed to determine efficacy and safety of oral miltefosine for the treatment of anthroponotic cutaneous leishmaniasis (ACL) cases who were refractory to MA in Iran. Methodology/Princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We found Miltefosine an effective drug for CL with prolong duration (p<0.023) and multiple lesions (p <0.001), emphasizing its coverage of all strains in KPK. Our results are endorsed by Ware JM et al and Tayyabi M et al 12,13 Ware JM concluded that miltefosine was effective (77℅) against all strains of leishmania, while Tayyab M et al found it effective (82℅) against MA-resistant cases of CL. Mann S et al reported successful treatment of two cases of L. panamensis, which is also consistent with our study results of our study.…”
Section: Table-1: Distribution Of Patients On the Basis Of Gender (N=74)supporting
confidence: 77%
“…We found Miltefosine an effective drug for CL with prolong duration (p<0.023) and multiple lesions (p <0.001), emphasizing its coverage of all strains in KPK. Our results are endorsed by Ware JM et al and Tayyabi M et al 12,13 Ware JM concluded that miltefosine was effective (77℅) against all strains of leishmania, while Tayyab M et al found it effective (82℅) against MA-resistant cases of CL. Mann S et al reported successful treatment of two cases of L. panamensis, which is also consistent with our study results of our study.…”
Section: Table-1: Distribution Of Patients On the Basis Of Gender (N=74)supporting
confidence: 77%
“…Miltefosine is also useful for drug-resistant cases of antimonials. 34 The therapeutic effects of oral drug miltefosine are comparable with other injectable therapies against leishmaniasis. 35 Therefore, in the case of leishmaniasis, the possibility of oral therapy is considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Old World cutaneous leishmaniasis (OWCL) is mainly seen in two clinical forms: zoonotic (rural type), which is caused by the Leishmania major species, and anthroponotic (urban type), which is caused by the Leishmania tropica species. 1 Although meglumine antimoniate (MA) remains the main treatment choice of OWCL, many patients are categorized as MA resistant. 1 Up to now, many therapeutic options have been explored in the treatment of MA-resistant CL.…”
mentioning
confidence: 99%
“…1 Although meglumine antimoniate (MA) remains the main treatment choice of OWCL, many patients are categorized as MA resistant. 1 Up to now, many therapeutic options have been explored in the treatment of MA-resistant CL. In this article, the therapeutic outcome of allopurinol plus itraconazole (API) was evaluated in 27 patients (56 lesions) with anthroponotic CL who were resistant to previous treatment with MA.…”
mentioning
confidence: 99%